New Discoveries in Directory (On the example of creative activity of Surkhandarya theater) - Faxriddin ABDUVOHIDOV (Zien Journals, 2021)
This article is devoted to years of research by the main director of the Surkhandarya Theater, Honored Artist of Uzbekistan Mansur Ravshan. Particular attention is paid to the analysis of the plays that have played a role in the development of the Surkhandarya Theater and the formation of its artistic image.
Keywords: Theater; drama; actor; director